Economics of development and planning - Agrawal, A. N. (Amar Nath); Lal, Kundan (New Delhi, India : Vikas Publishing House, 1993)
In this edition the book has been revised in the light of recent events and developments. The first chapter has been recast to include the newly developed Human Development Index by the United Nations. Three new chapters have been added to discuss the current much-debated issues relating to technological changes, foreign direct investment and environmental degradation.
Includes bibliographic references
rpm 18/04/2018
Loans
Keywords: Economic development; Economic policy